2011
DOI: 10.1063/1.3591905
|View full text |Cite
|
Sign up to set email alerts
|

Signal Evaluation System of Flexible Array Ect Probes for Inspecting Complexly Shaped Surfaces

Abstract: Articles you may be interested inDevelopment of flexible array eddy current probes for complex geometries and inspection of magnetic parts using magnetic sensors AIP Conf.ABSTRACT. We developed a signal evaluation system of flexible array eddy current testing (ECT) probes for inspecting complexly shaped metal surfaces. Our probes employ excitation and pickup coil pairs arrayed on a bendable substrate to measure curved targets. Since the developed probes produce signals due to the change in the relative positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
(2 reference statements)
0
7
0
Order By: Relevance
“…Nishimizu [11,12] detected cracks in a non-ferromagnetic material using an arrayed multi-coil probe with two scanning angles and demonstrated that the sensitivity was affected by the two angles. Mohseni [13] investigated the scanning angle for a ferromagnetic material with a split D-probe and found that the signal amplitude varied with the scanning angle.…”
Section: Introductionmentioning
confidence: 99%
“…Nishimizu [11,12] detected cracks in a non-ferromagnetic material using an arrayed multi-coil probe with two scanning angles and demonstrated that the sensitivity was affected by the two angles. Mohseni [13] investigated the scanning angle for a ferromagnetic material with a split D-probe and found that the signal amplitude varied with the scanning angle.…”
Section: Introductionmentioning
confidence: 99%
“…Although single element eddy current sensors and multi-element sensor arrays are both used for defect sizing, sensor arrays are more widely used because of their advantages such as higher detection efficiency and spatial resolution, and larger coverage [ 8 , 12 ]. Transmit/receive (T/R) type coil configurations have been proven to provide higher detection sensitivity and better signal-to-noise ratio, and thus have been widely used in eddy current sensors [ 16 ].…”
Section: Sensor Designmentioning
confidence: 99%
“…The probe was very sensitive to micro-defects, yet no quantitative detection results were disclosed. Endo, et al [ 12 ] designed a flexible array eddy current testing (ECT) probe, and a 12 decibel drop method was used to size fatigue crack length, with a sizing accuracy within ±3 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Further research in EC sensors led to development of flexible AEC [66][67][68] techniques where the array conforms to the inspected surface, improving the reliability and detection capabilities of the examination. The coils can be printed or etched on a substrate with diameters of approximately 1 mm or smaller.…”
Section: Figure 21 Examination Of Fatigue Crack and Surrounding Areamentioning
confidence: 99%